Numerical study of piston bowl geometries on PFI-HCCI engine performance - Nik Ab Rashid, Nik Muhammad Hafiz; Hairuddin, Abdul Aziz; Md Rezali, Khairil Anas; Masuri, Siti Ujila; A.A.Mossa, Muntasser (Universiti Malaysia Pahang Faculty of Mechanical Engineering, 2023)
Homogeneous charge compression ignition (HCCI) is an advanced combustion strategy proposed to provide higher efficiency and lower emissions than conventional compression ignition. However, there are still tough challenges in the successful operation of HCCI engines. Among these challenges, homogeneous mixture preparation and combustion phase control plays a vital role in determining the efficiency and emissions. Piston bowl geometry significantly enhances the process by improving the flow, turbulence, and mixing for the combustion. The study utilised experimental and numerical simulation methods to analyse HCCI combustion in port fuel injection (PFI) mode and evaluate the effect of piston geometries on engine performance. For this purpose, the different pistons bowl geometries (Baseline model, SQC, and CCC) with the same volume, compression, and equivalence ratio were numerically tested in a four-stroke, single-cylinder, YANMAR diesel engine. The numerical simulation results provide adequate assurance to proceed with the study with different piston geometries design. Compared to SQC and CCC, the Baseline model produced significantly higher cylinder pressure, temperature, and heat release rate. Different piston shape designs influenced the formation of air-fuel mixing, thereby affecting the time and location of onset combustion. The present investigation offered the significant role of piston geometry for the control mechanism of PFI-HCCI combustion, that is a vital part in demonstrating HCCI combustion.